Mapeamento da população idosa do município de Arapongas, Paraná - Stefanuto, Graziela (2012)
This study is the delineation of the elderly population, ie the population aged over 60 years. About this means that population aging has brought changes in morbidity and mortality profile of Brazilians. For the elderly population, these changes give rise to a new understanding of health care. In this respect, delve into the morbid issues of the elderly population becomes a key factor. Thus, this research shows the health profile of the elderly population of the city of Arapongas, located in the northern state of Parana. Aiming to investigate the population 60 years and more of the city of Arapongas, Pr, was used for primary and secondary sources to collect information about socio-demographic and health of 9295 elderly. The socio-demographic profile shows that most subjects of the research focuses on the range of 60 to 79 years, where the female is more often than males. Such as marital status, most are married, with schooling less than three years, living with a Family constellation of two people. Although retired, a significant portion assumes an alternative source of income. In the health profile, the study subjects did not use tobacco or alcohol, are independent, do not practice regular physical activity perceive their health as good or regular. For the indicators of morbidity, most subjects reported no falls, and when they occurred, did not cause fractures. To install the pathologies, chronic degenerative diseases were the most reported. Regarding the profile of causes of hospitalization Diseases of the circulatory system were the most frequent, followed by diseases of the digestive and external causes. It is concluded that the profile of subjects is similar to the findings in the literature, but the discrepancies found indicate a possible need for improvement in the accessibility of elderly health services.